Leadership metaphor explorer. creative conversations for better leadership - Palus, Charles J.; Horth, David M., 1945- (Center for Creative Leadership, 2012)
This publication is a comprehensive guide to complement a facilitator's use of the Leadership Metaphor Explorer tool - A dynamic, interactive tool designed to stimulate creative, insightful conversations in and among groups about leadership.